2017
DOI: 10.1097/igc.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastasis in Patients With Endometrioid Endometrial Cancer: Overtreatment Is the Main Issue

Abstract: The risk of lymph node involvement was 30%, even in patients with the highest-risk uterine factors, that is, those who had tumors of greater than 2 cm, deep myometrial invasion, and grade 3 disease, indicating that 70% of these patients underwent unnecessary lymphatic dissection. A precise balance must be achieved between the desire to prevent unnecessary lymphadenectomy and the ability to diagnose LNM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…On the contrary, patients who will not benefit from lymphadenectomy must be identified in order to minimize over-treatment and prevent lymphadenectomy-associated serious morbidities such as intraoperative bleeding, deep vein thrombosis, lymphocyst formation, lymphedema of lower extremities, and chylous ascites [ 15 ]. Since over-treatment is an important issue in the surgical management of endometrioid EC currently [ 5 ], a precise balance must be obtained between the desire to prevent over-treatment and the ability to diagnose LN involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, patients who will not benefit from lymphadenectomy must be identified in order to minimize over-treatment and prevent lymphadenectomy-associated serious morbidities such as intraoperative bleeding, deep vein thrombosis, lymphocyst formation, lymphedema of lower extremities, and chylous ascites [ 15 ]. Since over-treatment is an important issue in the surgical management of endometrioid EC currently [ 5 ], a precise balance must be obtained between the desire to prevent over-treatment and the ability to diagnose LN involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rate of LN involvement is approximately 15% in endometrioid EC [ 5 ], 75% of women with EC require systematic LN dissection (LND) when the Mayo criteria are used [ 3 ]. Lefringhouse et al [ 6 ] have recently reported that the Mayo algorithm performed well at identifying EC at high-risk of extra-uterine disease; however, by recommending lymphadenectomy for over two-thirds of their study population.…”
Section: Introductionmentioning
confidence: 99%
“…While studies tend to point to a lack of benefits of SL in cases of type 1 cancer restricted to the uterine body [[22], [23], [24], [25], [26], [27], [28]], there is no consensus about how to proceed when the EC had an intermediate risk, as the women evaluated here. Longitudinal evaluation of our data exhibited high 5-year survival rate for both groups, although significantly worse for women performed complete surgical staging, including DFS.…”
Section: Commentmentioning
confidence: 98%
“…Another result worth highlighting was the maintenance of the use of adjuvant radiotherapy even in women who underwent SL, which is currently less indicated in cases of negative lymphadenectomy and without associated risk factors, as guided by more recent studies [13,[26], [27], [28], [29], [30], [31]]. In this study, even in the SL group and considering only women without lymph node involvement, 52% received pelvic radiotherapy, although these were performed before 2010.…”
Section: Commentmentioning
confidence: 99%
“…In the absence of sentinel node biopsy, the choice on lymphadenectomy is guided through preoperative risk stratification, most often based on the tentative stage, histotype and grade 27 . The prevalence of lymph node metastases in endometrial cancer is 11-22% [28][29][30] . If the risk of lymph node metastases could be better predicted, many lymphadenectomies could be avoided.…”
Section: List Of Abbreviationsmentioning
confidence: 99%